2016
DOI: 10.1155/2016/2939087
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carnosine for Oxidative Stress Reduction in Different Pathologies

Abstract: The main properties and biological effects of the antioxidant carnosine, the natural dipeptide β-alanyl-L-histidine, are considered. Data on the effective use of carnosine in different pathologies are presented. Special attention is paid to issues of use of carnosine in neurologic and mental diseases, in alcoholism as well as in physiological states accompanied by activation of free-radical processes and formation of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 61 publications
3
77
0
4
Order By: Relevance
“…CAR enhances the activities of major antioxidant enzymes and prevents oxidation/glycation of cellular macromolecules, delaying aging . Several studies have found that CAR can prevent/treat pathologies involving oxidative stress . NAC has been used for decades in the treatment of several pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…CAR enhances the activities of major antioxidant enzymes and prevents oxidation/glycation of cellular macromolecules, delaying aging . Several studies have found that CAR can prevent/treat pathologies involving oxidative stress . NAC has been used for decades in the treatment of several pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antioxidative peptide in organism, mainly included carnosine and glutathione system. Carnosine is a kind of natural water-soluble dipeptide which has high effective bioactivity, can effectively eliminate oxygen derived free radicals, aldehydes, lipoidase, ROS and so on, with strong antioxidant activity [14] . Carnosine could inhibit intracellular peroxidation but to inhibit membranal peroxidation that it was able to inhibit every oxidation reaction of the whole peroxidation [15] .…”
Section: Discussionmentioning
confidence: 99%
“…It is easily absorbed in the digestive tract, penetrates the blood-brain barrier, and has high bioavailability and membrane-stabilizing action [169]. Carnosine is a known antioxidant and neuroprotective agent [170,171] and reduces inflammation and neurodegeneration by lowering TNF-α and nitric oxide synthesis [172].…”
Section: Supplementsmentioning
confidence: 99%